2019
DOI: 10.1002/jcp.28269
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluoride regulates the osteo/odontogenic differentiation of stem cells from apical papilla by modulating autophagy

Abstract: Fluoride (sodium fluoride) is thought to be essential in the development of tooth, and research shows that fluoride can modulate the differentiation of dental stem cells. However, the effects of fluoride on the committed differentiation of stem cells from apical papilla (SCAPs) and the underlying mechanisms remain unclear. Here, SCAPs were isolated from healthy extracted human third molars with immature roots and then were cultured with NaF conditioned media. Cell Counting Kit‐8, EdU staining, and flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Alkaline phosphatase (ALP) has a vital function during the formation of hydroxyapatite crystal, which is the initial phase in mineralization of osteoblasts and odontoblasts [26], and its activity is upregulated at an early stage of calcification [36]. Therefore, many studies used ALP as an early-stage marker of osteo/odontoblastic differentiation [25, 37]. In the present study, 0.2 mg/ml was the optimal concentration of BP-CM to promote differentiation of BMMSCs through detecting the ALP activity at days 3, 5, and 7, as well as the gene level of Alp at day 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline phosphatase (ALP) has a vital function during the formation of hydroxyapatite crystal, which is the initial phase in mineralization of osteoblasts and odontoblasts [26], and its activity is upregulated at an early stage of calcification [36]. Therefore, many studies used ALP as an early-stage marker of osteo/odontoblastic differentiation [25, 37]. In the present study, 0.2 mg/ml was the optimal concentration of BP-CM to promote differentiation of BMMSCs through detecting the ALP activity at days 3, 5, and 7, as well as the gene level of Alp at day 5.…”
Section: Discussionmentioning
confidence: 99%
“…TEM was performed to observe autophagosomes as described previously [25]. BMMSCs were harvested and fixed with 2.5% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence indicates that autophagy plays a crucial role in the regulation of bone homeostasis (Nollet et al, 2014;Gomez-Puerto et al, 2016). Autophagy enhances osteoblastic differentiation of BMSCs (Wan et al, 2017;Pan et al, 2019). Autophagy also regulates mesenchymal stem cell properties and senescence during bone aging (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is also an essential process that maintains mineralizing capacity, and balance the population of osteoblasts and osteoclasts [31]. The members in our team have demonstrated that autophagy is involved in the odontogenic and osteogenic differentiation in stem cells of apical papilla and rBMMSCs [32,33].…”
Section: Introductionmentioning
confidence: 93%